(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to identify the effect of using the (K U D) strategy in solving mathematical problems among primary school students, and in order to achieve the goal of the research, the following null hypothesis was developed: There is no statistically significant difference at the significance level (0.05) between the mean scores of the experimental group students who will study mathematics according to the (KUD) strategy and the scores of the control group students who will study the same subject according to the usual method in the test of solving mathematical problems. The research sample consisted of (67) female students of the fifth grade of primary school in (Sheikh Maarouf Elementary School) for the academic year (2020-2021), distributed into two groups, one of them experimental and studied according to the (KUD) strategy, with (34) female students and the other control, which were studied according to the usual method by (33) students. The two groups were rewarded in the variables (chronological age calculated in months, intelligence, academic achievement of the parents, previous knowledge in mathematics, and previous achievement in mathematics), as the research tool represented by (the test of solving mathematical problems) was built. The test of solving mathematical problems consisted of (16) objective items, and the validity of the test was verified, and the reliability coefficient was acceptable, as the KewderRichasson _20 equation was used to find it (0.85). After the end of the experiment, the test of solving mathematical problems was applied to each of the two groups (experimental and control), and using the appropriate statistical means, the results showed a statistically significant difference between the experimental and control groups in the test of solving mathematical problems in favor of the experimental group. In light of the research results, the researcher presented some recommendations and suggestions for the purpose of conducting subsequent research and studies.